HTTP over UDP: an experimental investigation of QUIC - Gaetano Carlucci; Luca De Cicco; Saverio Mascolo (Proceedings of the 30th Annual ACM Symposium on Applied Computing, 2015)
This paper investigates "Quick UDP Internet Connections" (QUIC), which was proposed by Google in 2012 as a reliable protocol on top of UDP in order to reduce Web Page retrieval time. We first check, through experiments, if QUIC can be safely deployed in the Internet and then we evaluate the Web page load time in comparison with SPDY and HTTP. We have found that QUIC reduces the overall page retrieval time with respect to HTTP in case of a channel without induced random losses and outperforms SPDY in the case of a lossy channel. The FEC module, when enabled, worsens the performance of QUIC.
Keywords: Congestion control; UDP; TCP; SPDY; QUIC; HTTP